Effects of Trace Rare Earth (TRE) additions on thermal, crystal structure, and radiation shielding properties of CuAlMn high-temperature S-M alloys: A closer look at Cerium effect - Kalay, Ece; Ozkul, Iskender; Karaduman, Oktay; Kizilgun, Yasin; Guler, Omer; Canbay, Canan Aksu; Tekin, H. O. (Pergamon-Elsevier Science Ltd, 2025)
This study systematically investigates the effect of Ce addition on the thermal, structural, and radiation shielding properties of CuAlMn-based high-temperature shape memory alloys (HTSMAs). Among the different compositions, Ce-III demonstrated the most balanced performance, exhibiting optimized phase transformation behavior, microstructural refinement, and enhanced gamma-ray attenuation. Differential Scanning Calorimetry (DSC) analysis revealed that Ce-III exhibited lower transformation temperatures, with austenite start (As) and finish (Af) temperatures of 378.13 degrees C and 429.75 degrees C, respectively, and martensite start (Ms) and finish (Mf) temperatures of 402.52 degrees C and 341.91 degrees C, suggesting improved thermal stability. Microstructural analysis indicated significant grain refinement, attributed to Ce's dislocation pinning effect, which contributed to enhanced strength and radiation attenuation. X-ray diffraction (XRD) patterns confirmed the formation of Ce-rich intermetallic phases, such as Mn1.15Cu3.85Ce and Cu8Ce4, which increased density and photon interaction probability. The Ce-III alloy exhibited superior linear attenuation coefficients and reduced half-value layer, reinforcing its effectiveness as a radiation shielding material. It can be concluded that Ce-III represents an optimal composition with a synergistic combination of structural stability, phase transformation control, and enhanced radiation shielding capabilities, making it a promising candidate for nuclear and high-radiation applications.
Keywords: High temperature shape memory alloys; Radiation shielding; Martensitic transformation; Ce addition; CuAlMn alloys